Biocha Soil Amendment: Effect on Soil, Crop Performance, and Diseases Resistance - Amare, Ermias Misganaw (International Journal on Food, Agriculture and Natural Resources, 2023)
One of the main challenges facing developing countries is an ever-increasing gap between population growth and food supply. Diseases, insects, and weeds decrease the production of crops worldwide by 36%. Hence, control of crop pests contributes to increased crop production. Organic amendments to the soil have direct impacts on crop productivity and plant health as it enhances soil fertility, water, and nutrient retention and plant disease defense mechanisms. Biochar is an important organic amendment. It is produced by the pyrolysis process, whereby organic substances are broken down at higher temperatures in low oxygen conditions. Biohar improved soil nutrient availability and water retention capacity, and induced plant resistance against broad ranges of plant pathogenic organisms including fungi, nematodes, and bacteria. Biochar soil amendment also enhances root-associated microbes such as flavobacterium and arbuscular mycorrhizae. Biochar amendments can increase soil essential nutrients for crop productivity and suppress plant pathogens. Suppression of plant pathogens is attributed to the stimulation of beneficial soil microbes, providing nutrients, and inducing plant defense. The objectives of the review are to depict the importance of biochar soil amendment on crop performance, disease resistance, and soil properties.